Clausal complementation in south Slavic - Wiemer, Björn 1966-; Sonnenhauser, Barbara 1975- (De Gruyter Mouton, 2022)
This volume assembles contributions addressing clausal complementation across the entire South Slavic territory. The main focus is on particular aspects of complementation, covering the contemporary standard languages as well as older stages and/or non-standard varieties and the impact of language contact, primarily with non-Slavic languages. Presenting in-depth studies, they thus contribute to the overarching collective aim of arriving at a comprehensive picture of the patterns of clausal complementation on which South Slavic languages profile against a wider typological background, but also diverge internally if we look closer at details in the contemporary stage and in diachronic development. The volume divides into an introduction setting the stage for the single case-studies, an article developing a general template of complementation with a detailed overview of the components relevant for South Slavic, studies addressing particular structural phenomena from different theoretical viewpoints, and articles focusing on variation in space and/or time
Keywords: Komplementarität; Slavische Sprachen; Sprachtypologie; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Südslawische Sprachen; Nebensatz; Ergänzung -- Linguistik; Aufsatzsammlung